Identification of Warbler species using Bioacoustics in Purna Wildlife Sanctuary, Gujarat, India - Maslehuddin, Ayesha Mohammad; Yahya, Hafiz Shaeque Ahmad; Jambu, Nikunj (Indian Forester, 2020)
Warblers are smallbirds thatmigrate in large flocks from theirbreeding grounds to many parts oflndia. Habitat preferences of these insectivorous birds vary from species to species. This study was conducted to identify different species ofwarblers in Purna Wildlife Sanctuary as the area serves as a wintering ground for many warbler species, but proper documentation had been lacking. Identification ofdifferentspecies ofwarblers is difficult morphologically; therefore, bioacoustics was used as a tool of identification. Seven species were identified using bioacoustics which belongs to the genus Acrocephalus and Phylloscopus in Purna Wildlife Sanctuary.